Guava (Psidium guajava L.) seed: A low-volume, high-value byproduct for human health and the food industry. (30th August 2022) - Kumar, Manoj; Kapoor, Swati; Dhumal, Sangram; Tkaczewska, Joanna; Changan, Sushil; Saurabh, Vivek; Mekhemar, Mohamed; Radha; Rais, Nadeem; Satankar, Varsha; Pandiselvam, R.; Sayed, Ali A.S.; et al.
Highlights: First review on nutritional, health promoting and food application of guava seed. Superior nutritional profile with respect to lipids, vitamins, and minerals. Guava seed extracts showed antioxidant, neuroprotective, and anticancer activities. Application of guava seeds as an ingredient in functional food is highlighted. Abstract: Guava processing industries generate peel and seeds as primary waste fractions. Guava seeds obtained after fruit processing possess untapped potential in the field of food science due to the presence of a diversity of nutritional and bioactive compounds. Along with offering a detailed understanding of the nutritional attributes of guava seeds, the present review comprehensively elaborates on the therapeutic activities of their bioactive compounds, their techno-functional properties, and their other edible and nonedible applications. The limited molecular and biochemical mechanistic studies outlining the antioxidant, immunomodulatory, anticancer, antimicrobial, neuroprotective and antidiabetic activities of guava seeds available in the literature are also extensively discussed in this review. The use of guava seed constituents as food additives and food functional and structural modulators, primarily as fat reducers, emulsifiers, water and oil holding agents, is also conceptually explained. Additional human intervention and molecular mechanistic studies deciphering the effects of guava seeds on various diseases and human health are warranted.